Analysis of Factors Affecting the Incidence of Dermatitis - Suryanda Suryanda; Nelly Rustiati; Ni Ketut Sujati (School of Health Sciences Al-Ma'arif, 2025)
Dermatitis is inflammation of the skin (epidermis and dermis) as a response to the influence of exogenous or endogenous factors, causing clinical abnormalities in the form of polymorphic efflorescence (erythema, edema, papules, vesicles, scale, lichenification) and complaints of itching. This research is to analyze the factors that influence the incidence of dermatitis in residents of Lubuk Batang village, Ogan Komering Ulu Regency. The sample size of this study was 68 people, it was a cross-sectional study. The research variables were history of allergies, type of food, occupation, use of contact materials with the incidence of dermatitis. There is a significant relationship between history of allergies and the incidence of dermatitis p-value=0.001, there is a significant relationship between type of food and the incidence of dermatitis p. value = 0.001, there is a significant relationship between the use of chemical products and the incidence of dermatitis p. value = 0.003. Meanwhile, there was no significant relationship between type of work and the incidence of dermatitis because p. value = 0.762. The majority of Lubuk Batang village residents who experience dermatitis are due to a history of allergies to certain foods or chemicals or contact materials. Meanwhile, the work of the majority of village residents as rubber tappers also carries a high risk of developing dermatitis